PS01.057: THYROIDECTOMY AND LARYNGO-PHARYNGEAL REFLUX: WHAT'S NEW. (14th September 2018) - Macaione, Ina; Cusimano, Alessia; Cipolla, Calogero; Graceffa, Giuseppa; Pantuso, Gianni; Fiorentino, Eugenio
Abstract: Background: 'Local neck symptoms' may be related to goiter; a persistence of those symptoms after an uncomplicated total thyroidectomy (TT) might be referred to the laryngo-pharyngeal reflux (LPR). Our previous study found a correlation between goiter and LPR in selected patients with local neck symptoms; the purpose of our current study is to investigate the presence of a laringopharyngitis in patients with goiter, before and after TT, even in the absence of local neck symptoms, assessing whether the presence of LPR may play a role at the outset of the symptomatology. Methods: Two groups of patients were considered and they differred for the presence or absence of local neck symptoms: group A (25 patients) and group B (40 patients). The clinical evaluation was standardized using the reflux symptom index. The patients were subjected to videolaringoscopy (VLS) and to esophageal videoflurography (VFGE) before and three months after surgery. Results: Before surgery all the patients in group A showed a normal vocal chord motility and laryngitis findings at the VLS. The VFGE was positive to abnormal swallowing in 86% of patients. The laryngitis findings at VLS, were found in 38% of cases in group B. At VFGE 96% of the patients were positive to the test. The symptoms reported in the pre-operative were unchanged after surgery in group A. In group B 63% of patients remained positive; at VFGE 73% had a clear pathological condition. Conclusion: In 2010 'Amelita' study concluded that LPR should be taken into account as a possible movens of post-thyroidectomy clinical picture, both in the diagnosis and in the therapeutic management of those patients who complained about local neck symptoms, since the only TT hadn't been effective. The collected data of the current study are consistent with those of the previous study: symptoms persisted or increased in laryngopharingeal reflux-positive patients, while in the control group the symptoms were absent or the new appearance symptomatic pictures were moderate. It is a shared view that we shouldn't wait for the overt clinical picture, but prevent it. It is essential to identify, through a careful pre-operative evaluation, patients positive to LPR. Disclosure: All authors have declared no conflicts of interest.